Preparation method of sodium ion positive electrode material, sodium ion positive electrode material and secondary battery

The preparation process of sodium ion positive electrode materials is simplified through wet coprecipitation and wet grinding processes, solving the existing problems of cumbersome and high cost, and achieving cost-effective preparation of positive electrode materials.

CN119683702APending Publication Date: 2025-03-25LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411592117.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The preparation process of existing sodium ion cathode materials is cumbersome and has high cost, making it difficult to improve cost performance.

Method used

The sodium ion positive electrode material is prepared by wet co-precipitation and wet grinding processes. Sodium hydroxide is used as a precipitant to simplify the process flow and reduce costs.

Benefits of technology

The process simplification and cost reduction are achieved, and the cost-effective sodium ion cathode material is prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683702A_ABST
    Figure CN119683702A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sodium ion positive electrode material, the sodium ion positive electrode material and a secondary battery. The preparation method of the sodium ion positive electrode material comprises the following steps: S1, preparing a precursor mother solution through wet coprecipitation; s2, adding a sodium source into the mother liquor, and obtaining slurry through a wet grinding process of sanding and spray drying; s3, the slurry obtained in the step S2 is dried and granulated, and powder is obtained; and S4, calcining and sintering the powder to obtain the positive electrode material. According to the preparation method of the sodium ion positive electrode material, the manufacturing process can be simplified, and the manufacturing cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a sodium ion positive electrode material, a sodium ion positive electrode material and a secondary battery. Background Art

[0002] Sodium ion positive electrode material is one of the core materials of sodium ion batteries. Currently, the raw materials of sodium ion oxide positive electrode materials are cheap, but their production and manufacturing process is highly similar to that of lithium-ion secondary batteries, especially the material preparation process, which requires cumbersome processes and high processing fees, making it difficult to achieve cost advantages. Therefore, it is necessary to develop a more cost-effective preparation process. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a method for preparing a sodium ion positive electrode material, which can solve the technical problems of complicated process and high cost.

[0004] According to the first aspect of the present invention, the method for preparing a sodium ion positive electrode material comprises the following steps: S1, preparing a precursor mother liquor by wet coprecipitation; S2, adding a sodium source to the mother liquor, and obtaining a slurry by a wet grinding process; S3, drying and granulating the slurry obtained in step S2 to obtain a powder; S4, calcining and sintering the powder to obtain a positive electrode material.

[0005] In the preparation method of the sodium ion positive electrode material of the embodiment of the present invention, before sintering, wet coprecipitation and wet grinding processes are adopted. Among them, wet coprecipitation has the advantages of simple steps, can achieve raw material impurity removal and uniform mixing of coprecipitated atoms; wet grinding has the advantages of low technical threshold and simple operation. In this embodiment, by integrating the two processes of wet coprecipitation to prepare the precursor and wet grinding, it has the advantages of simple raw materials and simplified process routes, and can prepare a positive electrode material with high cost performance.

[0006] According to some embodiments of the present invention, in step S1, sodium hydroxide is used as a precipitant, and the mother liquor has a precipitate and a suspended substance.

[0007] According to some embodiments of the present invention, in step S1, the sulfate raw material containing the metal element M is configured into a solution, and after adding alkali solution, a metal salt precipitate is obtained. After adding sodium hydroxide alkali solution until no more precipitate is generated, the mother liquor is obtained by filtering and washing.

[0008] According to some embodiments of the present invention, the positive electrode material is Na x MO2, where 0.66≤x≤1.

[0009] According to some embodiments of the present invention, in step S1, the mother liquor has 4 μm≤D50≤10 μm, 7<pH<13, and a sulfate mass content of <0.1%; in step S2, the slurry has D50<1 μm, 10<pH<13; in step S3, the powder has 15 μm<D50<30 μm, and 0.5<AD<1.

[0010] According to some embodiments of the present invention, in step S2, grinding is performed by sand milling and spray drying to obtain a slurry.

[0011] According to some embodiments of the present invention, the sodium source is sodium carbonate.

[0012] According to some embodiments of the present invention, in step S3, the slurry is dried and granulated by spray drying granulation to obtain a powder.

[0013] The sodium ion positive electrode material according to the second embodiment of the present invention includes a positive electrode material prepared by any of the above-mentioned methods for preparing the sodium ion positive electrode material.

[0014] The sodium ion secondary battery according to the third aspect of the present invention comprises any of the above-mentioned sodium ion positive electrode materials.

[0015] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 This is a SEM morphology image of Example 2 of the present invention. DETAILED DESCRIPTION

[0017] Reference below Figure 1 A method for preparing a sodium ion positive electrode material according to an embodiment of the present invention is described.

[0018] The method for preparing the sodium ion positive electrode material according to an embodiment of the present invention comprises the following steps: S1. Preparing a precursor mother solution T by wet coprecipitation; S2, adding a sodium source to the mother liquor T, and obtaining a slurry through a wet grinding process; S3, drying and granulating the slurry obtained in step S2 to obtain a powder; S4, calcining and sintering the powder to obtain the positive electrode material. That is, in step S4, the powder is directly calcined to obtain the positive electrode material.

[0019] That is to say, in the preparation method of the sodium ion positive electrode material of the embodiment of the present invention, before sintering, the process of wet coprecipitation and wet grinding is adopted. Among them, wet coprecipitation has the advantages of simple steps, can achieve the advantages of raw material impurity removal and uniform mixing of coprecipitation atoms; wet grinding has the advantages of low technical threshold and simple operation. In this embodiment, by integrating the two processes of wet coprecipitation to prepare the precursor and wet grinding, it has the advantages of simple raw materials and simplified process routes, and can prepare a positive electrode material with high cost performance.

[0020] According to one embodiment of the present invention, in step S1, sodium hydroxide is used as a precipitant, and the mother liquor has precipitates and suspended matter. That is, wet precipitation is used in step S1, and sodium hydroxide is used as a precipitant.

[0021] It is understood that, on the one hand, the wet co-precipitation process used in the prior art generally includes the following steps: (1) Sulfate, alkali solution precipitant and specific complexing agent, control pH, feeding rate, solid-liquid volume, temperature, stirring speed, inert atmosphere protection measures and other indicators to achieve co-precipitation of multiple metal elements to obtain a spherical precursor mother solution; (2) The mother liquor is centrifuged, filtered, washed multiple times, and dried under atmosphere protection conditions to obtain a powder precursor, and the product is a hydroxide or carbonate with a relatively high purity; (3) The precursor, additives, a small amount of doped main element and sodium salt are fully mixed and stirred; (4) The positive electrode material is prepared by high-temperature calcination.

[0022] It is understandable that the wet co-precipitation process of the prior art has the following characteristics: the co-precipitation conditions have high technical barriers, are relatively difficult, and have high additional costs. The advantages are that metal sulfates are mass commodities with relatively low prices, and impurities in the raw materials can be removed by co-precipitation, filtration and washing, and the metal raw materials can achieve atomic-level mixing effects, which is conducive to the preparation of high-performance positive electrode materials with higher purity.

[0023] In comparison, the wet coprecipitation of the embodiment of the present application uses sodium hydroxide as a precipitant, and there is no need to refer to the traditional coprecipitation process, deliberately control pH, temperature, stirring speed, precipitation time, atmosphere protection and other measures, and there is no need to add specific complexing agents and ammonia, etc., only sodium hydroxide is needed as a precipitant, which is easy to operate, has low difficulty, and has low time and energy consumption, which can further reduce the cost of the wet coprecipitation process of the prior art. In addition, in the present embodiment, the product obtained in step S1 is not a traditional spherical precursor powder, but a mother liquor T with precipitates and suspended matter. In addition, sodium hydroxide is used as a precipitant in step S1, so that the main components in the mother liquor are loose amorphous hydroxides and soluble sodium salts and a small amount of other metal raw materials, so only simple grinding is required to achieve a dispersion effect, so this step can also save energy consumption and time.

[0024] In some specific embodiments of the present invention, in step S1, the sulfate raw material containing the metal element M is configured into a solution, and after adding alkali solution, a metal salt precipitate is obtained, and after adding sodium hydroxide alkali solution until no more precipitate is generated, filtering and washing to obtain a mother liquor T. For example, the wet precipitation process of this embodiment can be specifically as follows: the sulfate raw material containing the required main metal component is dissolved into a solution according to the element ratio, the alkali solution is slowly added and stirred to generate a metal salt precipitate, the sodium hydroxide alkali solution is continuously added until no more precipitate is generated, filtering to obtain a fixed ratio concentrated slurry, and the sulfate in the filtered slurry is washed with pure water for multiple times and finally configured into a precipitate suspension mother liquor T with pure water.

[0025] According to one embodiment of the present invention, the positive electrode material is Na x MO2, wherein 0.66≤x≤1, M is a metal element, for example, M is Ni, Fe, Mn, Cu, Al, Zr, Ti, etc. x is 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or 1, etc. In this embodiment, by using a positive electrode material that conforms to the above chemical formula, it can be achieved that all conventional layered oxide positive electrode materials can be applicable to the wet co-precipitation process of the embodiment of the present invention.

[0026] In some specific embodiments of the present invention, in step S1, the 4μm≤D50≤10μm of the mother liquor, for example, the D50 of the mother liquor is 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, etc. It can be understood that, firstly, the particle size of the precursor mother liquor affects the subsequent wet grinding efficiency. Precursors with small particle sizes are more easily broken and refined during wet grinding, but too small particle sizes lead to greater process difficulties; secondly, the precursors with moderate particle sizes in this embodiment are easy to fully contact with the grinding media, for example, to achieve the purpose of uniform mixing with sodium carbonate. 7<pH<13, for example, pH is 7.1, 7.2, 7.3, 7.5, 8.5, 9, 10, 11 or 12, etc., and the alkaline environment needs to be ensured for wet co-precipitation with hydroxide as a precipitant, but it should not be too high. In addition, it can be understood that, firstly, a pH greater than 7 is conducive to creating an alkaline environment, ensuring that the transition metal forms precipitation and tends to form a spherical precursor; secondly, if the pH is too low, it is easy to cause the secondary spherical particles to agglomerate, and if it is too high, it is easy to cause the crystal nucleus to grow too fast and eventually lead to uneven particle size; thirdly, the OH in the mother liquor - It is easy to cause small particles to agglomerate, making the particle size distribution wider. The mass content of sulfate (SO4 2- %) < 0.1%, for example, the mass content of sulfate is 0.09%, 0.08%, 0.07%, 0.06%, 0.05% or 0.04%, etc., where SO4 2- From transition metal salts and impurities, they need to be removed through filtering and washing. If SO4 2- Residues in the precursor, if the content is too high, it is easy to affect the structure of the positive electrode material and thus the capacity, and even react with other components in the battery, increasing the potential safety hazards of the battery. 2- %)<0.1, the lower the content, the better the final product quality and battery safety can be guaranteed. In addition, in this embodiment, D50, pH, SO4 2- The content is within the above range, which can ensure the uniformity of the precursor particles in step S1, provide a stable precursor for subsequent wet grinding and granulation, and reduce the impurity content, which is beneficial to the capacity of the positive electrode material.

[0027] According to one embodiment of the present invention, in step S2, D50 in the slurry is less than 1 μm, for example, D50 of the slurry is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm, etc., wet grinding is conducive to ensuring D50 less than 1 μm, and when the D50 of the slurry is too large, there is a problem of difficulty in atomization, and it is also easy to cause the performance of the material to deteriorate. Therefore, in this embodiment, the above D50 is used to form uniform and fine droplets, achieve rapid drying and obtain products with uniform particle size. 10<pH<13, for example, pH is 10.5, 11, 11.5, 12, 12.5, etc., which can ensure the alkaline environment of the slurry and avoid the risk of degradation of the hydroxide precursor. In addition, it should be noted that the pH value should not be too large, which is easy to cause corrosion to the equipment. For example, in step S2, the solid-liquid ratio can be controlled to be 0.4-1.0 during the feeding process, and the final slurry has a D50 of less than 1 μm and a slurry pH of more than 10. The slurry satisfies the D50 and pH requirements within this range, which is beneficial to the formation of droplets and particle uniformity during the spray drying process, and reduces the occurrence of side reactions.

[0028] In some specific embodiments of the present invention, in step S3, 15μm<D50<30μm in the powder, for example, D50 in the powder is 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm or 29μm, etc. It should be noted that since the D50 of the spray-dried powder affects the subsequent sintering, if the particle size is too small, the crystal particles grow too fast during calcination, resulting in the enlargement of the finished particles, affecting the subsequent capacity and rate performance; if the particle size is too large, the sintering difficulty is higher; therefore, in this embodiment, the use of the above-mentioned powder of appropriate size is beneficial to the optimization of the sintering machine performance. 0.5<loose density AD<1, for example, AD is 0.6, 0.7, 0.8 or 0.9, etc. It should be noted that if AD is too low, it is easy to cause low filling volume and reduced production capacity. If AD is too high, there are fewer gaps between particles, and the contact surface with air is reduced during sintering and cannot fully react, which ultimately leads to unqualified electrochemical performance of the product. In this embodiment, the spray-dried powder meets the above-mentioned D50 and AD requirements at the same time, and can meet the sintering requirements to obtain a suitable particle size and uniform product while improving product performance and production capacity.

[0029] According to one embodiment of the present invention, grinding is performed by sand milling and spray drying in step S2 to obtain a slurry. That is to say, wet grinding is specifically achieved by sand milling and spray drying. For example, the wet grinding process adopted includes: transferring the mother liquor T obtained by wet precipitation to a sand milling and spray drying raw material storage tank, and adding pure water, sodium carbonate and other small amounts of main elements, and additives according to the required proportions, wherein the additives are metal oxides, hydroxides, carbonates, etc. It can be understood that, except for the necessary sodium source, other additives and small amounts of main elements are selectively added.

[0030] Among them, the wet grinding process in the prior art generally includes the following steps: (1) Various oxide raw materials are put into the sand mill together and wet-grinded to obtain slurry. The process requires controlling the purity and grinding particle size of various raw materials; (2) transferring the ground slurry to the spray drying process for spray drying and granulation; (3) The spray-dried granulated product is directly calcined at high temperature to prepare the positive electrode material.

[0031] The existing wet grinding process has the following characteristics: since it does not include an impurity removal step, it is often necessary to strictly control the purity of the raw materials. At the same time, some oxide raw materials often have large particle hardness and are relatively difficult to grind. In addition, relatively pure oxide raw materials are often prepared by precipitation of sulfate alone. Therefore, the cost of the process itself is not high, but the additional cost of preparing purer positive electrode materials is high, and there is also a certain quality risk. The advantages are that there is no need for a co-precipitation process, the technical threshold is low, the material ratio is flexible, and there are more optional raw materials.

[0032] In comparison, in this embodiment, wet grinding is achieved by sand milling and spray drying, and the coprecipitated precursor is used as the transition metal source for grinding, which solves the problem that the purity of various oxide raw materials is difficult to ensure and the grinding is difficult. In addition, sand milling can usually produce very fine particles, and the grinding medium can effectively impact and shear the material under the action of high-speed rotation or vibration, thereby achieving particle size refinement.

[0033] In some specific embodiments of the present invention, the sodium source is sodium carbonate. Compared with other sodium salts, the advantages of sodium carbonate include but are not limited to: first, the impurities produced by calcination are gaseous CO2 and have been discharged, while other sodium salts are prone to the presence of anionic impurities; second, the preparation is simple and the cost is low.

[0034] According to one embodiment of the present invention, in step S3, the slurry is dried and granulated by spray drying granulation to obtain a powder. That is to say, in this embodiment, before sintering, wet co-precipitation, wet grinding and spray drying granulation pre-treatment processes are adopted. During operation, the slurry can be directly fed into the spray drying equipment. In this embodiment, by adopting the spray drying granulation process, compared with the dry mixing process, the particle size of the spray dried material is more uniform, which is conducive to improving the bulk density of the powder and the bulk density of the finished product; in addition, the process is simple, and compared with other granulation processes, evaporation, crushing and other processes are omitted; and the drying speed is fast, instant drying, the droplets are atomized, and the particles are finer.

[0035] The present invention also discloses a sodium ion positive electrode material, including a positive electrode material prepared by the method for preparing the sodium ion positive electrode material of any of the above embodiments. Since the method for preparing the sodium ion positive electrode material of any of the above embodiments has the advantages of low production cost and simple process, the sodium ion positive electrode material of the embodiment of the present invention has the advantages of low price, etc., which will not be elaborated here.

[0036] The present invention also discloses a sodium ion secondary battery, which includes the sodium ion positive electrode material of any of the above embodiments. The sodium ion secondary battery of the embodiment of the present invention also has the advantage of low cost.

[0037] The following describes in detail the method for preparing the sodium ion positive electrode material, the sodium ion positive electrode material and the sodium ion secondary battery of the embodiments of the present invention in conjunction with specific embodiments.

[0038] Example 1 The positive electrode material in Example 1 is Na 0.66 Ni 0.33 Mn 0.66 Fe 0.01 O2, the preparation method comprises the following steps: S1. Dissolve the industrial raw materials nickel sulfate and manganese sulfate (or nickel sulfate and manganese sulfate containing crystal water) in a metal molar ratio of 0.33:0.67 to prepare a 0.5 mol / L solution, slowly add 0.1 mol / L sodium hydroxide solution to the solution and stir to generate metal salt precipitation, continue to add sodium hydroxide solution until no precipitation is generated, and obtain a thick slurry. Wash and filter the sulfate in the slurry with pure water, repeat 3 times, and finally add appropriate amount of pure water to obtain the slurry obtained as the mother liquor T of the suspension, and test the particle size and pH value of the mother liquor T, as well as the mass content of sulfate in the mother liquor. The index parameters are: D50=3.2μm, pH=8.1, SO4 2- %=0.08%; S2, transfer the mother liquor T to the sand mill spray drying raw material storage tank, and according to the molecular formula Na 0.66 Ni 0.33 Mn0.66 Fe 0.01 Sodium carbonate and ferric oxide were added to the required metal ratio of O2, and finally pure water was added to dilute to obtain slurry G, so that the solid-liquid ratio was 0.4, and the slurry was ground to D50 = 0.82 μm, and the pH was measured to be 10.9; S3, feed the slurry G directly into the spray drying equipment, spray dry granulation, obtain spray dried material H, test the powder H particle size value D50 = 26.2μm, loose density AD = 0.86; S4. The powder H is directly calcined to prepare the positive electrode material. The sintering conditions are: 950°C high temperature and air atmosphere insulation for 15 hours to obtain the target material and obtain the positive electrode material.

[0039] Comparative Example 1-1 In Comparative Example 1-1, conventional coprecipitation process was used to prepare Na 0.66 Ni 0.33 Mn 0.66 Fe 0.01 O2, the preparation method comprises the following steps: (1) Purchase Ni for market commercialization 0.33 Mn 0.66 Spherical precursor of (OH)2 and D50 = 5 μm; (2) Ni 0.33 Mn 0.66 (OH)2 is mixed with a corresponding proportion of sodium carbonate and a small amount of the main element ferric oxide, and the material to be sintered is obtained; (3) The positive electrode material was prepared by the same calcination process as in Example 1.

[0040] Comparative Example 1-2 In Comparative Example 1-2, conventional sand mill spray drying process was used to prepare Na 0.66 Ni 0.33 Mn 0.66 Fe 0.01 O2, the preparation method comprises the following steps: (1) According to the corresponding element ratios, industrial raw materials nickelous oxide, manganese tetraoxide, ferric oxide, and sodium carbonate were put into a sand mill, and pure water was added to maintain the same solid-liquid ratio of 0.4 as in Example 1. The same sand milling process as in Example 1 was used to grind the slurry to D50 = 0.8 μm; (2) The slurry is directly fed into the spray drying equipment for spray drying and granulation. The spray dried material is obtained by the same spray drying process. The test results show that D50 = 25 μm and the bulk density AD = 0.87; (3) The positive electrode material was prepared by the same calcination process as in Example 1.

[0041] Example 2 In Example 2, the same method and steps as in Example 1 were used to prepare Na1Ni 0.3 Fe 0.3 Mn 0.335 Cu 0.05 Zr 0.002 Al 0.001 Ti 0.012 O2 positive electrode material, wherein a corresponding proportion of sodium carbonate, a relatively small amount of main element Cu, and trace amounts of additives Zr, Al, and Ti are added in the sand grinding and spray drying process of step S2, and Cu is selected from copper oxide, Ti is selected from titanium dioxide, and Al is selected from aluminum oxide. Other conditions are consistent with those in Example 1 to prepare the positive electrode material.

[0042] Comparative Example 2-1 In Comparative Example 2-1, the same positive electrode material as in Example 2 was prepared by referring to the preparation method and steps of Comparative Example 1-1.

[0043] Comparative Example 2-2 In Comparative Example 2-2, the same positive electrode material as in Example 2 was prepared by referring to the preparation method and steps of Comparative Example 1-2.

[0044] Example 3 In Example 3, Na was prepared by the same method and steps as in Example 1. 0.96 Ni 0.4 Mn 0.4 Cu 0.08 T 0.12 O2 positive electrode material, wherein the sand grinding and spray drying in step S2 only adds sodium carbonate, the nickel, manganese, copper and titanium in Example 3 are all high-content main elements, without additives and trace main elements, and other conditions are consistent with Example 1 to prepare the positive electrode material.

[0045] Comparative Example 3-1 In Comparative Example 3-1, the same positive electrode material as in Example 3 was prepared by referring to the preparation method and steps of Comparative Example 1-1.

[0046] Comparative Example 3-2 In Comparative Example 3-2, the same positive electrode material as in Example 3 was prepared by referring to the preparation method and steps of Comparative Example 1-2.

[0047] The positive electrode materials of the above-mentioned embodiment and comparative example were used to prepare button cells, and the preparation method of the button cell included the following steps: the positive electrode material, SP and PVDF were mixed in a mass ratio of 90:5:5, NMP was added to make a viscous glue, coated on aluminum foil, and baked in a vacuum drying oven at 120°C for 12 hours to obtain a positive electrode sheet. A metal sodium sheet was used as a counter electrode, glass fiber (Waterman) was used as a diaphragm, 1 mol / L NaPF6, EC:DMC (volume ratio) = 1:1 was configured as an electrolyte, and a 2032 button cell was assembled in an Ar protection glove box.

[0048] In addition, at least a portion of the following tests were performed on the positive electrode materials and 2.5-4.0V button batteries of the above embodiments and comparative examples: (1) First charge (first charge) and first discharge (first discharge) test: According to the corresponding voltage range, charging is performed with a small current of 0.1C and discharging is performed with a small current of 0.1C (unit: mAh / g); (2) First efficiency: The first efficiency is calculated from the button battery’s 0.1C discharge capacity / 0.1C charging capacity in the first week (unit: %). (3) Particle size test: Malvern particle size analyzer was used to measure the particle size (D5, unit: μm); (4) Bulk density test: Use a conventional bulk density meter to test (AD, unit: g / cm 3 ) (5) Sulfate content test: conventional ICP tester (unit: %) (6) pH test: conventional pH tester; (7) Solid-liquid ratio test: Take an appropriate amount of stable slurry, weigh it, dry it and dehydrate it, weigh it again, and calculate the solid-liquid ratio based on the two weight data; (8) SEM morphology test: obtained by scanning electron microscope test.

[0049] The key process indicators of the above embodiments and comparative examples are summarized in Table 1, and the product test data are summarized in Table 2.

[0050] Table 1. Key process parameters What needs to be explained about Table 1 is: (1) In the mother liquor T of Examples 1, 2, and 3, the core monitoring indicator of the precipitation process is the sulfate content. The sulfate content is controlled to be less than 0.1% by washing and filtering, i.e., at a relatively small value. It should be noted that SO4 2- / % content refers to the sulfate in the mother liquor T compared to the solid content in the mother liquor T, which is obtained by ICP test and conversion. In addition, there is no specific restriction on the particle size D50. The D50 obtained by the test basically satisfies D50<10μm and pH value>7, which is achieved by adding excessive alkali solution and washing with pure water for many times. Similarly, pH is only limited to a wide range, that is, pH>7.

[0051] (2) Particle size D50 and SO4 of Comparative Examples 1-1, 2-1, and 3-1 2- / % content values ​​are all test values. The precursor powders in each comparative example are industrialized precursors, and the particle size is the conventional 5μm particle size, while SO4 2- / % content exists as impurities and the tested value is a typical value.

[0052] (3) Data description of slurry G and spray-dried material H in Examples 1, 2, 3, and Comparative Examples 1-2, 2-2, and 3-2: The measured pH of the process basically satisfies pH>10, and the sodium carbonate added in the process causes the pH to be at a relatively high level; regarding the particle size D50 and the solid-liquid ratio, according to the grinding capacity control of the sand mill, the basic D50 range satisfies D50<1μm and the solid-liquid ratio is between 0.4 and 1.0; the loose density AD and particle size D50 of the spray-dried material are both test values.

[0053] In addition, in order to compare data such as impurity content more objectively, the raw materials used in this scheme are all industrial sulfates, oxides, sodium carbonate, and precursors sold in the market, not laboratory analytical grade reagents.

[0054] Table 2. Key product indicators The following conclusions can be drawn from Table 2: (1) Compared with Comparative Examples 1-1, 2-1, and 3-1, the precursor processes used in Examples 1, 2, and 3 separately show that Examples 1, 2, and 3 all show the same level as the comparative examples in terms of first charge, first discharge, and first efficiency, that is, the difference in electrical properties between the two is not large; further, in terms of the content of sulfate ions as an impurity, each Example reaches a level equivalent to that of the precursor; from the perspective of bulk density AD, the bulk density of each Example is higher than that of the comparative example, which means that the Example has a higher volume energy density. Therefore, from the perspective of volume energy density, the Example is superior. Considering the technical threshold and the difficulty of operation, the process of Examples 1, 2, and 3 is superior to that of Comparative Examples 1-1, 2-1, and 3-1.

[0055] (2) Compared with Comparative Examples 1-2, 2-2, and 3-2, Examples 1, 2, and 3, which separately adopt the traditional sand mill spray drying process, show that Examples 1, 2, and 3 are slightly better than the comparative examples in terms of first charge, first discharge, and first effect. Furthermore, in terms of the content of impurity sulfate, the examples are significantly better than the comparative examples. The reason is that the conventional industrial oxide raw materials used in the comparative examples have relatively more impurities, and there is no impurity removal step in the whole process. Therefore, the comparative examples show a higher impurity content. From the perspective of bulk density AD, the two are at a comparable level. Therefore, from the perspective of performance, impurity content, etc., it can be judged that the processes of Examples 1, 2, and 3 are better than those of Comparative Examples 1-2, 2-2, and 3-2.

[0056] In addition, the SEM morphology of Example 2 was tested, and the test results were as follows: Figure 1 As shown, it is shown that the process produces a sodium ion positive electrode material with a single crystal morphology. Compared with the conventional oxide sand milling spray drying process and the precursor dry mixing process, the process described in this scheme obtains a powder with more uniform particles and a higher bulk density, which is conducive to its full reaction in the subsequent sintering process, optimizes the single crystal morphology, and ultimately increases the bulk density of the product, thereby increasing its volume energy density.

[0057] In summary, the method for preparing the sodium ion positive electrode material according to the embodiment of the present invention can simplify the production process and reduce the production cost by combining the wet coprecipitation and wet grinding processes.

[0058] Other structures and operations of the battery according to the embodiment of the present invention are known to those skilled in the art and will not be described in detail here.

[0059] In the description of the present invention, it is necessary to understand that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "inside", "outside", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0060] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0061] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0062] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a sodium ion positive electrode material, characterized in that: The steps include: S1. preparing a precursor mother solution by wet coprecipitation; S2, adding a sodium source to the mother liquor, and obtaining a slurry through a wet grinding process; S3, drying and granulating the slurry obtained in step S2 to obtain a powder; S4, calcining and sintering the powder to obtain a positive electrode material.

2. The method for preparing a sodium ion positive electrode material according to claim 1, characterized in that: In step S1, sodium hydroxide is used as a precipitant, and the mother liquor has a precipitate and a suspended substance.

3. The method for preparing a sodium ion positive electrode material according to claim 2, characterized in that: In step S1, a sulfate raw material containing a metal element M is prepared into a solution, and after adding an alkaline solution, a metal salt precipitate is obtained. After adding sodium hydroxide alkaline solution until no more precipitate is generated, the mother liquor is obtained after filtering and washing.

4. The method for preparing the sodium ion positive electrode material according to claim 3, characterized in that: The positive electrode material is Na x MO2, where 0.66≤x≤1.

5. The method for preparing the sodium ion positive electrode material according to claim 4, characterized in that: In step S1, the mother liquor has 4μm≤D50≤10μm, 7<pH<13, and a sulfate mass content of<0.1%; in step S2, the slurry has D50<1μm, 10<pH<13; in step S3, the powder has 15μm<D50<30μm, 0.5<AD<1.

6. The method for preparing the sodium ion positive electrode material according to claim 1 or 5, characterized in that: In step S2, grinding is performed by sand milling and spray drying to obtain a slurry.

7. The method for preparing a sodium ion positive electrode material according to claim 1, characterized in that: The sodium source is sodium carbonate.

8. The method for preparing a sodium ion positive electrode material according to claim 1, characterized in that: In step S3, the slurry is dried and granulated by spray drying and granulation to obtain a powder.

9. A sodium ion positive electrode material, characterized in that: A positive electrode material prepared by the method for preparing a sodium ion positive electrode material according to any one of claims 1 to 8.

10. A sodium ion secondary battery, characterized in that: Comprising the sodium ion positive electrode material according to claim 9.